In Vivo Bioavailability of Selenium in Selenium-Enriched Streptococcus thermophilus and Enterococcus faecium in CD IGS Rats - Krausova, Gabriela; Kana, Antonin; Vecka, Marek; Hyrslova, Ivana; Stankova, Barbora; Kantorova, Vera; Mrvikova, Iva; Huttl, Martina; Malinska, Hana (Antioxidants, 2021)
The selenium (Se) enrichment of yeasts and lactic acid bacteria (LAB) has recently emerged as a novel concept; the individual health effects of these beneficial microorganisms are combined by supplying the essential micronutrient Se in a more bioavailable and less toxic form. This study investigated the bioavailability of Se in the strains Enterococcus faecium CCDM 922A (EF) and Streptococcus thermophilus CCDM 144 (ST) and their respective Se-enriched forms, SeEF and SeST, in a CD (SD-Sprague Dawley) IGS rat model. Se-enriched LAB administration resulted in higher Se concentrations in the liver and kidneys of rats, where selenocystine was the prevalent Se species. The administration of both Se-enriched strains improved the antioxidant status of the animals. The effect of the diet was more pronounced in the heart tissue, where a lower glutathione reductase content was observed, irrespective of the Se fortification in LAB. Interestingly, rats fed diets with EF and SeEF had higher glutathione reductase activity. Reduced concentrations of serum malondialdehyde were noted following Se supplementation. Diets containing Se-enriched strains showed no macroscopic effects on the liver, kidneys, heart, and brain and had no apparent influence on the basic parameters of the lipid metabolism. Both the strains tested herein showed potential for further applications as promising sources of organically bound Se and Se nanoparticles.